Symbolisme og sanselighet i Knut Hamsuns Victoria (1898): En økokritisk lesning - Wærp, Henning Howlid (Nordlit, 2020)
Hamsun's novel Victoria is a story of jealousy between the miller's son Johannes, Victoria, the daughter raised on the estate, and the officer Otto. It is also a novel about Johannes' development as an author. The article examines the relationship between Johannes as a keen observer of phenomena in nature – taking note of scents and visual impressions, sounds and tactile sensations - and his imagination, his dreams and visions. The hypothesis is that Johannes in his relationship with the natural surroundings of his rural village develops what in ecocriticism is termed an ecological self, and that this distinguishes him – in a positive manner – from his rival Otto.
Keywords: Knut Hamsun; Victoria; Økokritikk; Symbolisme; Rosa